Effects of ibrutinib on proliferation and histamine release in canine neoplastic mast cells. (13th August 2019) - Gamperl, Susanne; Stefanzl, Gabriele; Peter, Barbara; Smiljkovic, Dubravka; Bauer, Karin; Willmann, Michael; Valent, Peter; Hadzijusufovic, Emir
Abstract: The Bruton's tyrosine kinase (BTK) inhibitor ibrutinib is effective in the treatment of human chronic lymphocytic leukaemia and mantle cell lymphoma. Recent data have shown that ibrutinib also blocks IgE‐dependent activation and histamine release in human basophils (BAs) and mast cells (MCs). The aim of this study was to investigate whether BTK serves as a novel therapeutic target in canine mast cell tumours (MCTs). We evaluated the effects of ibrutinib on two canine MC lines, C2 and NI‐1 and on primary MCs obtained from canine MCTs (n = 3). Using flow cytometry, we found that ibrutinib suppresses phosphorylation of BTK and of downstream STAT5 in both MC lines. In addition, ibrutinib decreased proliferation of neoplastic MCs, with IC50 values ranging between 0.1 and 1 μM in primary MCT cells and between 1 and 3 μM in C2 and NI‐1 cells. In C2 cells, the combination "ibrutinib + midostaurin" produced synergistic growth‐inhibitory effects. At higher concentrations, ibrutinib also induced apoptosis in both MC lines. Finally, ibrutinib was found to suppress IgE‐dependent histamine release in primary MCT cells, with IC50 values ranging from 0.05 to 0.1 μM in NI‐1 cells, and from 0.05 to 1 μM in primary MCT cells. In summary, ibrutinib exerts anti‐proliferative effects in canine neoplastic MCs and counteracts IgE‐dependent histamine release in these cells. Based on our data, ibrutinib may be considered as a novel therapeutic agent for the treatment of canine MCT. The value of BTK inhibition in canine MCT patients remains to be elucidated in clinical trials.